WEBSITE UNTUK PENDATAAN BALITA POSYANDU CEMPAKA RW 11 KELURAHAN ANTAPANI KIDUL KOTA BANDUNG - Nita Nurliawati; Aulya Fitriana; Andi Saputra; Dharina Khamelia; Mutia Salsabila; Nahbisaila; Sherli Berliana (Setia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2023)
Posyandu Cempaka in RW 11, Antapani Kidul Village, Antapani District, Bandung City has a low to moderate maternal and infant participation rate of 40% to 45%. In addition, the growth and development of toddlers is recorded manually or manually on the health card page (KMS). The absence of KMS often makes it difficult for parents and posyandu staff to find history about their child's development. This activity aims to increase the number of toddlers who come to Posyandu. In addition, this activity aims to make it easier for parents of toddlers to obtain information about Posyandu action plans, information on child growth and development, as well as Posyandu health information and programs. As for posyandu cadres, this activity can help collect data and report child growth and development, and can facilitate reporting to the sub-district or puskesmas. This activity utilizes the method of applying technology by creating a Posyandu Website. This website is a collection of components consisting of text, images, sound, and animation so it is interesting to visit (Sholechul Azis, 2013). The electronic-based data collection method serves as the basis for activity planning and implementation. Based on the measurement results, this community service activity is able to fulfill all indicators of success, including: the number of mothers of children under five who use the application reaches 45%, the number of children under five who come to Posyandu increases by 75%, all children under five at Posyandu Cempaka are registered digitally, the level of community satisfaction is high , and the activity suitability level reached 100%.